Conférence: «Science politique et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Geneviève Pagé, membre de l'Institut de recherches et d'études féministes et professeure au Département de science politique.
Keywords: approches et analyses; discipline; genre; histoire du féminisme; identités LGBTQIA2+; inégalités; militance; rapports sociaux de sexe; ressource en ligne; science politique; science politique et droit; sexisme; sexualité; systèmes d'oppressions; thématiques

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Consuming Ecstasy: Representations of Male and Female Orgasm in Mainstream Pornography - Séguin, Léa J.; Rodrigue, Carl; Lavigne, Julie (The Journal of Sex Research, 2018)
Social representations, which appear in a variety of media, can influence the way sexual experiences are perceived and understood. While pornography is not the only medium in which orgasm is portrayed, it is the most explicit, and it is widespread and easily accessible. As such, pornography is an ideal medium for examining representations of male and female orgasm. PornHub’s 50 most viewed videos of all time were viewed and coded for the frequency of male and female orgasm, orgasm-inducing sex acts (and whether activity inducing female orgasms included some form of clitoral stimulation), and auditory (verbal, vocal) and visual (bodily) indicators of orgasm. Content analysis was used to code and analyze the data. Results were analyzed in light of sexual script theory and previous orgasm research. Only 18.3% of women, compared to 78.0% of men, were shown reaching orgasm. Sex differences in depictions of orgasm, beyond the appearance of semen, were documented. Results support the male performance script as evident in pornographic depictions of orgasm, as well as coital and orgasm imperatives. As a result, representations of male and female orgasm in mainstream pornography may serve to perpetuate unrealistic beliefs and expectations in relation to female orgasm and male sexual performance.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; cours; discipline; orgasme; premier cycle; périodes historiques; rapports sociaux de sexe; représentation; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques